Teacher Experiences of Physical Education, Sports and Health Teaching in Elementary: Challenges and Strategies - Handayani, Widiyantari Sri; Rochmawan, Alfian Eko; Amin, Lailla Hidayatul (Universitas Pahlawan Tuanku Tambusai, 2024)
This study explores teachers’ experiences teaching Physical Education, Sports, and Health (Physical education) in elementary schools, highlighting the challenges and strategies used to overcome them. Physical education is an important part of the elementary education curriculum that aims to develop students’ physical, mental, and social health. However, teachers often face various obstacles, including limited sports facilities, minimal time allocation, and a lack of support from schools and parents. In addition, students’ perceptions that Physical education is a less important subject than other subjects also add to the difficulties in the teaching process. Teachers adopt more creative strategies to overcome these challenges, such as interactive learning approaches, integrating Physical education with other subjects, and utilizing digital technology. Teachers collaborate with other teachers and involve parents and the community in sports activities to increase student participation. This study uses a qualitative method with a case study approach, where data is collected through interviews and direct observation. The results show that despite facing various challenges, Physical education teachers successfully implement innovative strategies that effectively improve the quality of learning. This research is expected to provide useful insights for developing a better Physical education program in the future. Keywords: Physical education, Teaching strategies, Teacher Challenges; Elementary schools.